EVALUASI ADAPTASI MARGINAL BAHAN PENUTUPAN PIT DAN FISURA MELALUI GAMBARAN SCANNING ELECTRON MICROSCOPE (SEM) - Iin Sundari; Diana Setya Ningsih; Misra Hanum (Journal of Syiah Kuala Dentistry Society, 2018)
Pit and fissure are varies in shape and depth. Tooth with deep and narrow pit and fissure are susceptible for food and baterial retention that leads to caries formations, so it needs prevention treatment with more effective method such pit and fissure sealant. This study aimed to obtain information about marginal adaptation as mean value of distance between enamel surface and pit and fissure sealant by using Scanning Electron Microscope (SEM). Samples were 4 maxillary premolars with deep and narrow pit and fissure which were applied composite resin (3M ESPE Clinpro) and GIC (Fuji VII) as sealants. Specimens were stored for 24 hours and 1 month in incubator with temperature of 37C and were immersed in 5% methylene blue solution for 24 hours, then were observed under SEM. Analysis result showed mean value of distance between enamel surface and pit and fissure sealants resin based were 1.79 0.026 m after 24 hours application and 1.37 0.004 m after 1 month application while on GIC based were 33.37 1.520 m after 24 hours application and 3.6925 0.710 m after 1 month application. Conclusion of this study, there were a difference mean value of distance between enamel surface and sealants composite resin based and GIC based, where smaller distance was showed after 1 month application than 24 hours application.Keywords: pit and fissure sealants, marginal adaptation, and Scanning Electron Microscope (SEM).